Performance Evaluation on Printing Machine Goss Universal Using Reliability Availability Maintainability (RAM) Analysis and Overall Equipment Effectiveness (OEE) - Wulandari, Sari; Saputra, Muhammad Tamami Dwi; Alhilman, Judi; Athari, Nurdinintya (School of Industrial and System Engineering, Telkom University, 2017)
The development of science and technology that has been developed more rapidly at this time, along with the increasing need for information itself. By producing a newspaper every day then the states forced PT Pikiran Rakyat to further improve the smoothness, the effectiveness and efficiency of the printing. One way to measure the performance of machines in general by using OEE and to minimize the possibility of losses to be borne by the company is improving the Reliability, Availability and Maintainability (RAM). By using the data in the form of MTTF (Main Time to Failure) and MTTR (Main Time To Repair) of each subsystem of the printing press. Based on calculations using the method of Overall Equipment Effectiveness, by performing calculations based on three main parameters with a study for eight months or 5760 hours, show that the value of the Availability of 75%, the value of the Performance of 97%, and the value of Quality by 98%, then the system has OEE values of 71.60%. The system has a reliability score of 10.59% at 70 hours based on the analytical approach. Maintainability calculations using modeling reliability block diagram, it is found that the entire unit in the system has a chance to settle down a minimum of 12 hours to be able to function again with a probability of 100% to reach its original state. During the eight-month study, Inherent Availability of the system is 99.52% based on analytical approach and Operational Availability of the system is 73.91%. Keywords—Reliability, Availability, Maintainability, OEE, MTTF, MTTR